2018
DOI: 10.1001/journalofethics.2018.20.3.sect1-1803
|View full text |Cite
|
Sign up to set email alerts
|

Should Race Be Used as a Variable in Research on Preterm Birth?

Abstract: Racial variations in preterm birth (PTB) outcomes are well described, but causal mechanisms linking race and PTB are not. In clinical research, race is typically treated as representing fixed biological traits. In reality, race is a social construct that approximates lived experiences of historical and ongoing systematic discrimination and, in the case of PTB, particular stressors of black womanhood and reproduction. These experiences are embodied as adverse multigenerational health outcomes. Race thus present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Evaluating maternal race as a social construct and component of psychosocial stress is one area of this research in particular that needs more attention. Race is frequently used as a covariate or confounding variable in models assessing epigenomic outcomes in human studies but is rarely treated as a social exposure despite differences in lived experiences across races due to increased risk of environmental exposures, experiences of racism, and reduced opportunities [ 57 , 58 ]. Future studies should not only evaluate placental epigenomics and infant health outcomes in the context of race as a social construct but also recruit cohorts that accurately model the racial diversity of the general population.…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%
“…Evaluating maternal race as a social construct and component of psychosocial stress is one area of this research in particular that needs more attention. Race is frequently used as a covariate or confounding variable in models assessing epigenomic outcomes in human studies but is rarely treated as a social exposure despite differences in lived experiences across races due to increased risk of environmental exposures, experiences of racism, and reduced opportunities [ 57 , 58 ]. Future studies should not only evaluate placental epigenomics and infant health outcomes in the context of race as a social construct but also recruit cohorts that accurately model the racial diversity of the general population.…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%
“…Risk factors for preterm birth include advanced maternal age, self-reported race and ethnicity, a plurality of births, co-morbidities, a prior preterm birth history, and environmental or social factors [ 8 ]. In particular, previous studies have shown that the use of self-reported race and ethnicity is a risk factor for preterm birth and approximates lived experiences of systemic discrimination and racism [ 9 13 ]. Evidence on the role of chronic exposure to stress includes the effect of “weathering” and the increased allostatic load of stress experienced by women of color as well as changes seen to the hypothalamic-pituitary axis and immune system that may lead to preterm birth [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%